INTERPRETATION OF HISTORICAL AND CULTURAL HERITAGE IN THE WORKS OF CHINGIZ AKHMAROV - Salikhov, Omonilla (Current Research Journal of History, 2021)
This article discusses the interpretation of historical and cultural heritage in the works of Chingiz Akhmarov. In the genre of portraiture, folk art is approached with high skill, revealing the characteristic features of its national bright patterns. The perfect study of the human image in his portraits achieves a full disclosure of the psyche of the aesthetic, spiritual world of the heroes of the work. Without repeating the miniature, he takes a unique artistic approach, based on the poetic plastic conditionality, artistic space and form, the decorative principle of composition, as well as the rich thinking color of medieval masters, linear graphics.